Childhood bullous pemphigoid in a four-month-old child. - Pai, V.V.; Sori, T.; Kikkeri, N.N.; Athanikar, S.B.; Dinesh, U.S.; Rai, V. (European Journal of Pediatric Dermatology, 2012)
Bullous pemphigoid is an autoimmune subepidermal blistering disorder that mainly affects elderly. It is very rarely reported in infants. Herein we report a case of infantile bullous pemphigoid.